Tropomyosin 1: multiple roles in the developing heart and in the formation of congenital heart defects - England, Jennifer; Granados-Riveron, Javier T.; Polo-Parada, Luis; Kuriakose, Diji; Moore, Christopher; Brook, J. David; Rutland, Catrin S.; Setchfield, Kerry; Gell, Christopher; Ghosh, Tushar K.; Bu'Lock, Frances A.; Thornborough, Christopher; et al. (Elsevier, 2017)
Tropomyosin 1 (TPM1) is an essential sarcomeric component, stabilising the thin filament and facilitating actin's interaction with myosin. A number of sarcomeric proteins, such as alpha myosin heavy chain, play crucial roles in cardiac development. Mutations in these genes have been linked to congenital heart defects (CHDs), occurring in approximately 1 in 145 live births. To date, TPM1 has not been associated with isolated CHDs. Analysis of 380 CHD cases revealed three novel mutations in the TPM1 gene; IVS1 + 2T > C, I130V, S229F and a polyadenylation signal site variant GATAAA/AATAAA. Analysis of IVS1 + 2T > C revealed aberrant pre-mRNA splicing. In addition, abnormal structural properties were found in hearts transfected with TPM1 carrying I130V and S229F mutations. Phenotypic analysis of TPM1 morpholino-treated embryos revealed roles for TPM1 in cardiac looping, atrial septation and ventricular trabeculae formation and increased apoptosis was seen within the heart. In addition, sarcomere assembly was affected and altered action potentials were exhibited. This study demonstrated that sarcomeric TPM1 plays vital roles in cardiogenesis and is a suitable candidate gene for screening individuals with isolated CHDs.